EFFECT OF MARKET STRUCTURE ON BANK PERFORMANCE IN COMMERCIAL BANKS IN EAC COUNTRIES - Ketyenya, Dr. Rutto Peter (European Journal of Business and Strategic Management, 2017)
Purpose: The purpose of this study was to analyze effect of market structure on bank performance in commercial banks in EAC countries Methodology: The study used cross country data analysis of 100 commercial banks and collected secondary data from annual published audited financial statements for the period 1997-2011 Results: The results indicate that there was positive and significant relationship between economic growth and performance measures. Policy recommendation: The study recommended that the Central bank should follow the performance levels from both the productivity and profitability aspects as a way of monitoring individual bank performance levels so as to boost economic growth in the economy